2017
DOI: 10.1038/s41598-017-05300-5
|View full text |Cite
|
Sign up to set email alerts
|

Location Sensitive Deep Convolutional Neural Networks for Segmentation of White Matter Hyperintensities

Abstract: The anatomical location of imaging features is of crucial importance for accurate diagnosis in many medical tasks. Convolutional neural networks (CNN) have had huge successes in computer vision, but they lack the natural ability to incorporate the anatomical location in their decision making process, hindering success in some medical image analysis tasks. In this paper, to integrate the anatomical location information into the network, we propose several deep CNN architectures that consider multi-scale patches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
154
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(156 citation statements)
references
References 103 publications
(125 reference statements)
2
154
0
Order By: Relevance
“…Similar to the work of Ghafoorian et al, 8 we added explicit zone information to the first dense layer. The DCE-MRI and DWI streams with input sizes of (32 × 32 × 12) had 9 convolutional layers combining of (3 × 3 × 1) and (3 × 3 × 3) filter sizes.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to the work of Ghafoorian et al, 8 we added explicit zone information to the first dense layer. The DCE-MRI and DWI streams with input sizes of (32 × 32 × 12) had 9 convolutional layers combining of (3 × 3 × 1) and (3 × 3 × 3) filter sizes.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have also shown that deep learning technologies are on par with radiologists’ performance for both detection 36 and segmentation 37 tasks in ultrasonography and MRI, respectively. For the classification tasks of lymph node metastasis in PET-CT, deep learning had higher sensitivities but lower specificities than radiologists 38 .…”
Section: Ai In Medical Imagingmentioning
confidence: 99%
“…Beside these topics, there are many other examples: a methodology to estimate the uncertainty of the prediction that artificial intelligence model generates; principled way to integrate clinical or medical knowledge into the model training; development of content-based case retrieval system that searches images of similar diseases or conditions; efficient analysis of higherdimensional medical image, such as contrast enhanced images or follow-up images; and research on the privacy and security related to medical images when training and implementing artificial intelligence models [28,43,44,45,46]. These topics have not been thoroughly studied, and larger-scale studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…In a study done by Ghafoorian et al, a network architecture based on multi-scale T1 and FLAIR MR patches was proposed to segment and quantify white matter hyperintensities, which are related to various brain disorders [28]. When they compared various structures that combine data from multiple scales, the multi-scale late fusion with weight sharing (MSWS) structure, which shares the CNN feature extraction weights and fuses the features for the final segmentation, showed the best performance.…”
Section: Lesion Segmentationmentioning
confidence: 99%